Novel approach to neutron electric dipole moment search using weak measurement. (17th May 2021) - Ueda, Daiki; Kitahara, Teppei
Abstract: We propose a novel approach in a search for the neutron electric dipole moment (EDM) by taking advantage of signal amplification in a weak measurement, known as weak value amplification. Considering an analogy to the weak measurement that can measure the spin magnetic moment interaction, we examine an experimental setup with a polarized neutron beam through an external electric field with spatial gradient, where the signal is sensitive to the EDM interaction. In particular, a dedicated analysis of effects from impurities in pre- and post-selections is performed. We show that the weak value amplification occurs where the signal is enhanced by up to two orders of magnitude, and demonstrate a potential sensitivity of the proposed setup to the neutron EDM.